A scoring system to predict the elevation of mean pulmonary arterial pressure in idiopathic pulmonary fibrosis. Issue 1 (18th January 2018) - Furukawa, Taiki; Kondoh, Yasuhiro; Taniguchi, Hiroyuki; Yagi, Mitsuaki; Matsuda, Toshiaki; Kimura, Tomoki; Kataoka, Kensuke; Johkoh, Takeshi; Ando, Masahiko; Hashimoto, Naozumi; Sakamoto, Koji; Hasegawa, Yoshinori
Elevated mean pulmonary arterial pressure (MPAP; ≥21 mmHg) is sometimes seen in patients with idiopathic pulmonary fibrosis (IPF) and has an adverse impact upon survival. Although early diagnosis is crucial, there is no established screening tool that uses a combination of noninvasive examinations. We retrospectively analysed IPF patients at initial evaluation from April 2007 to July 2015 and, using logistic regression analysis, created a screening tool to identify elevated MPAP. Internal validation was also assessed for external validity using a bootstrap method. Using right-heart catheterisation (RHC), elevation of MPAP was determined to be present in 55 out of 273 patients. Multivariate models demonstrated that % predicted diffusing capacity of the lung for carbon monoxide ( D LCO ) <50%, ratio of pulmonary artery diameter to aorta diameter (PA/Ao) on computed tomography (CT) ≥0.9 and arterial oxygen tension ( P aO2 ) <80 Torr were independent predictors. When we assigned a single point to each variable, the prevalence of elevation of MPAP with a score of zero, one, two or three points was 6.7%, 16.0%, 29.1% and 65.4%, respectively. The area under curve (AUC) for the receiver operating characteristic (ROC) curve was good at 0.757 (95% CI 0.682–0.833). A simple clinical scoring system consisting of % predicted D LCO, PA/Ao ratio on CT and P aO2 can easily predict elevation of MPAP in patients with IPF. A simple scoring system comprising three variables can predict the likelihood of elevation of MPAP in IPF http://ow.ly/kZjA30haKvo